Kebahagiaan Dosen UIN Sunan Ampel Surabaya - Rizma Fithri (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2020)
Abstract : The purpose of this research to understand the picture of the happiness lecturer of civil servants and non-civil servants are there surroundings Islamic University of Sunan Ampel Surabaya country. The sample used as many as 75 of the subject lecturer of civil servants and non-civil servants, with random sampling techniques in 9 faculties. Data analysis techniques using descriptive statistics. The results of this study brings out the score's happiness of any professors of civil servants or non civil servants of 9 faculties, score range from number 1-6. Score 1-2 illustrates the level of happiness